Advances in clinical application on nursing intervention for ribavirin-associated adverse events - Jiang, Li-Li; Wang, Qing; Zhang, Jia-Xin; Fan, Jing-Hui; Li, Jing (Frontiers in Pharmacology, 2025)
Ribavirin is a broad-spectrum antiviral drug used to treat chronic hepatitis C, respiratory syncytial virus infections, and other viral diseases. However, its clinical use is often limited by adverse events, including hemolytic anemia, gastrointestinal disturbances, and neurological symptoms, which negatively affect treatment adherence and patient well-being. Nursing interventions are essential in mitigating these adverse events through early assessment, symptom management, patient education, and multidisciplinary collaboration, ultimately improving patient outcomes. Current evidence shows that nursing interventions significantly improve treatment efficacy and quality of life. However, challenges persist, such as individual patient variability, resource constraints, and insufficient evidence-based guidelines. Future research should focus on establishing standardized nursing protocols, conducting multicenter clinical studies, exploring intelligent nursing approaches, and enhancing nursing expertise to optimize ribavirin-related adverse event management.